Entrepreneurial Profile. A Confirmatory Factor Analysis of Entrepreneurial Attitude Orientation Scale (EAO) in Peruvian University Students - VARGAS-MERINO, JORGE ALBERTO (2022)
“Entrepreneurship is a possible solution that can guarantee labour insertion, but also allows its inclusion in disparate societies. also allows its inclusion in disparate societies. The aim of the study was to validate by means of a confirmatory factor analysis a measurement model to determine the profile of the university entrepreneur that from the constructs proposed in the Entrepreneurial Attitude Orientation Scale (EAO) can be tested in the university context in particular. The study corresponds to a quantitative approach, non-experimental design, cross-sectional, carried out in a private university in Lima, Peru, where 271 undergraduate and postgraduate students were selected. A confirmatory factor analysis was carried out to check the sustainability of the instrument. The proposed model corroborated the main fit indicators of the confirmatory factor analysis, the covariances between constructs are highly significant and positive, so the structure is confirmed by the data. The findings allow us to approve and corroborate the empirical sustainability of the Entrepreneurial Attitude Orientation Scale (EAO) for the entrepreneurial profile model in Peruvian university students.“